Determinants of Financial Technology Usage Intention: The Role of Trust, Ease of Use, and Perceived Risk - Alya Farika (CV. Megantara Abdi Nusa, 2026)
This study aims to analyze the influence of trust, ease of use, and perceived risk on the intention to use financial technology among users of digital financial services. The research employed a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the SmartPLS application. The data were collected from 200 respondents selected through purposive sampling, with the criteria of having used fintech services and being at least 17 years old. The research instrument was developed based on indicators adapted from previous studies and measured using a five-point Likert scale. The model testing results indicate that trust has a positive and significant effect on usage intention with a coefficient value of 0.412, ease of use has a positive and significant effect with a coefficient of 0.536, while perceived risk has a negative and significant effect with a coefficient of -0.287. The R-square value of 0.742 shows that the three independent variables explain 74.2% of the variance in financial technology usage intention. These findings suggest that enhancing security, improving system usability, and reducing perceived risk are strategic factors in promoting the adoption of digital financial services in society